FORMATIVE ASSESSMENT IN SCIENCE: AN EXEMPLAR - Koul, Anjni (SCHOOL SCIENCE, 2010)
Evaluation is a systematic process for collecting, analysing and interpreting evidences of learners’. It needs to be integrated with the process of teaching and learning. Evaluation should facilitate all-round development of the child, for that, formative system of evaluation has to be encouraged.